Nonvolatile Memory from Single-walled Carbon Nanotube-based Field Effect Transistors - Wang, Sigen; Sellin, Paul; Zhang, Qing; Yang, Dajiang (Current Nanoscience, 2005)
Nonvolatile memory from carbon nanotube-based field effect transistors (CNTFETs) was investigated in this paper. The CNTFETs were fabricated employing a single-walled carbon nanotube produced by arc-discharge technique, followed by the lift-off process. Hysteresis was clearly observed in the curve of the drain current versus gate voltage, which makes the CNTFET possible for a nonvolatile memory cell. It was also found that the environmental molecules including water and alcohol evidently affected the memory windows. The roles of the water and alcohol molecules in memory effect were discussed.
Keywords: CNTFETs